CONTROL OF Vibrio alginolyticus INFECTION IN ASIAN SEA BASS Lates calcarifer USING AMBON BANANA PLANT POWDER Musa paradisiacal THROUGH THE FEED - Hamida Pattah; Dinamella Wahjuningrum; Munti Yuhana; Widanarni Widanarni (Indonesian Aquaculture Journal, 2020)
Asian sea bass is one of economically important commodities in aquaculture. However, its culture often challenged by vibriosis infection which resulted in lower production. The study aimed to evaluate the effectiveness of the ambon banana plant powder application in feed as an effort to control the disease caused by Vibrio alginolyticus infection. Asian sea bass with total length of 7.48 ± 0.45 cm. Five different treatments were applied in this experiment, i.e. positive control, negative control, prevention, curative, and antibiotic application. The challenge test is carried out on the 15th day. Challenge test was performed with intramuscularly injection of V. alginolyticus at the cell density of 106 CFU/fish. The results showed the amount of feed consumption after the challenge test was highest in the curative and antibiotic control. However, these results were not significantly different (P>0.05) among preventive and curative treatments but were significantly different from controls (P<0.05). Fish treated with supplemented feed showed the highest total erythrocytes, total leukocytes, hemoglobin, respiratory burst, and lysozyme activity compared to controls. IL-1b gene expression increased after the challenge test with the highest level of expression in the curative treatment. It can be concluded that the administration of ambon banana plant powder (3 g/100 g diet) could control of V. alginolyticus infection in Asian sea bass and resulted 70.00% survival rate on prevention and 83.33% on curative treatments.